Persepsi Generasi Muda terhadap Budaya Maren dalam Bingkai Bhineka Tunggal Ika - Rumheng, Pieter; Suarniati, Ni Wayan; Pribadi, Nukhan Wicaksana (Jurnal Likhitaprajna, 2021)
Maren culture is a tradition of the people of the Kei archipelago, especially in the community in Ohoi Ur-Island, in the form of mutual cooperation, please help fellow citizens. This culture has existed since their ancestors. However, in this era of modernization and globalization, Maren culture has begun to fade. Thisi studyi aimsi are: (1) toi determinei the younger generation's perceptioni of Maren culture, (2) to know how to develop Maren cultural values to support the values of Bhineka Tunggal Ika through a qualitative approach. The resultsi showedi ithat: (1) The younger generation's perception of Maren culture is that it is a habit or way of life of the community to relieve the help of others by working together, (2) How to develop Maren culture to support the value of Bhineka Tunggal Ika, namely (a). The local government, namely the Regent and Mayor of Tual in Southeast Maluku Regency, must be able to issue a regional regulation that can build public awareness of the importance of Maren culture, (c). For parents or traditional leaders and the community, they are re-applying the real Maren culture so that it can be seen and passed on by the younger generation.